Implications of Persistent HPV52 and HPV58 Positivity for the Management of Cervical Lesions - Yi, Baozhu; Xu, Qian; Zhang, Zhixuan; Zhang, Jinyi; Xu, Yi; Huang, Luoqi; Hu, Yue; Tu, Quanmei; Chen, Jingyun (Frontiers in Oncology, 2022)
Objective To explore the guiding significance of human papillomavirus type 52 and 58 positivity in the stratified management of cervical lesions and to explore the appropriate management model.Method Retrospective analysis of 1616 patients attending the Second Hospital of Wenzhou Medical University from September 2014 to December 2020 were used as study subjects, 376 patients were HPV16 positive and TCT negative, 285 patients were HPV18 positive and TCT negative, 619 patients were HPV52 positive and TCT negative, and 336 patients were HPV58 positive and TCT negative, and colposcopic biopsy pathology results were used as the gold standard for statistical analysis.Result Among TCT-negative patients, HPV16-positive patients with high-grade cervical intraepithelial lesions and cervical cancer detected by biopsy had the highest detection rate of 21.81% (82/376), followed by HPV58-positive patients (36/336, P<0.001), then HPV18-positive patients (17/285, P<0.001), and finally HPV52-positive patients (32/619, P<0.001). P<0.001).Conclusion Patients positive for HPV16 /18 infection are referred immediately for colposcopy. patients positive for HPV58 and negative for TCT may have appropriate relaxed indications for colposcopy, especially if vulvar and vaginal lesions are possible. patients positive for HPV52 and negative for TCT may be considered for review follow-up and colposcopy if necessary.